Thyroid disorders as predictors of cemiplimab efficacy in recurrent/metastatic cervical cancer: real-world evidence from Poland - Pacholczak-Madej, Renata; Lisik-Habib, Maja; Mądry, Radosław; Szarszewska, Monika; Borysiewicz, Zuzanna; Gabalewicz, Katarzyna; Iwańska, Ewa; Szatkowski, Wiktor; Puskulluoglu, Mirosława; Jakubowicz, Jerzy; Blecharz, Paweł (Frontiers in Immunology, 2025)
IntroductionImmune checkpoint inhibitors have improved survival in patients with recurrent or metastatic cervical cancer (r/mCC), yet reliable predictors of treatment efficacy remain undefined. Immune-related adverse events (irAEs) have been suggested as potential predictors of response, but evidence in cervical cancer is limited.MethodsWe conducted an ambispective, multicenter observational study of 37 patients with r/mCC treated with cemiplimab within Poland’s national rescue access program. Baseline characteristics, treatment outcomes, and irAEs were analyzed. Survival outcomes were estimated using the Kaplan–Meier method and compared using Cox proportional hazards models. A p-value of <0.05 was considered statistically significant.ResultsAfter a median follow-up of 9.2 months, 17 episodes of irAEs were reported in 40.5% of patients (n=15), with thyroid disorders being the most common (n=11, 64.7%). Patients who developed ir-thyroid disorders had significantly longer progression-free survival (hazard ratio [HR]=0.2; 95% confidence interval [CI]: 0.07–0.6, p=0.004) and overall survival (HR=0.2; 95% CI: 0.05–0.9; p=0.04) compared to those without such events. Moreover, the objective response rate was notably higher in this group (45.5% versus 11.5%, p=0.04). Most irAEs were mild and manageable, with a median time to onset of two months after cemiplimab initiation.ConclusionsIr-thyroid disorders may indicate enhanced immune activation and represent a potential surrogate of cemiplimab efficacy in r/mCC, although validation in larger cohorts is required.